2016
DOI: 10.4012/dmj.2015-398
|View full text |Cite
|
Sign up to set email alerts
|

The effect of resin infiltration <i>vs.</i> fluoride varnish in enhancing enamel surface conditions after interproximal reduction

Abstract: To assess the effect of resin infiltration vs. fluoride varnish in enhancing enamel surface conditions after interproximal reduction (IPR). After IPR procedures, 84 human enamel specimens were divided into three groups, group A/ group B was treated by fluoride varnish/resin infiltration according to the manufacturers' instructions, group C were treated with nothing. All the specimens were pH-cycled twice daily in 37°C bath for 30 days. Surface micro-hardness, density and mineral loss were measured before and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 29 publications
3
12
1
2
Order By: Relevance
“…state in their study that fluoride varnish and resin infiltration may provide an enamel protection from acid challenge. Both treatments enhanced the surface microhardness of the enamel after interproximal reduction [16]. Their results are in accordance with ours, particularly for the protective effect on enamel that we found in our research with Profluorid® varnish.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…state in their study that fluoride varnish and resin infiltration may provide an enamel protection from acid challenge. Both treatments enhanced the surface microhardness of the enamel after interproximal reduction [16]. Their results are in accordance with ours, particularly for the protective effect on enamel that we found in our research with Profluorid® varnish.…”
Section: Discussionsupporting
confidence: 92%
“…In addition to their remineralizing action resulting from ion release, it is likely that these products act as a physical barrier that protects the enamel against acid attack [11]. Although the use of varnishes to prevent white spots during orthodontic treatment has been widely investigated [12,13,14,15], their effects following interproximal reduction procedures–as far as we are aware–have been studied just by Peng et al [16]. They measured microhardness, density and mineral loss after using a fluoride varnish and resin infiltration on stripped enamel surfaces [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the tested enamel was treated with one of infiltration resin, CPP-ACP or fluoride, it was found that infiltration resin had the strongest effects on the maintenance of micromorphology and the increasement of microhardness of irradiated enamel. In agreement with our findings, previous studies reported that the effects of infiltration resin on the surface microhardness of demineralized enamel was better than that of fluoride 29) and CPP-ACP 30) , which was closely related to the highly permeability of infiltration resin.…”
Section: Discussionsupporting
confidence: 93%
“…It has been shown that the use of fluoride varnishes contributes to a reduction in the incidence of caries, and so its application is recommended as a public health measure 8 , 9 . In orthodontics, these varnishes have been used to prevent white spot lesions during treatments involving brackets 10 , to resolve the lesions when they appear after treatment 11 , 12 and following interproximal enamel reduction 13 , 14 . However, as far as we are aware, no research has been published on the application of fluoride varnish after bracket removal as a preventative measure against demineralization.…”
Section: Introductionmentioning
confidence: 99%